Development of a Network Design Tool for the Herman-Beta Extended Transform - Khan, Isma-Eel (Department of Electrical Engineering, 2024)
The Herman-Beta method has been one of the most important network planning tools used in South Africa. Over decades, it has transformed from being able to perform probabilistic load flow studies for LV passive feeders to an algorithm capable of performing PLF studies for passive/active feeders of any voltage. Furthermore, the new algorithm reformulated the equations used to dispose of the underlying assumptions used in the original method. This reformulation came to be known as the Herman-Beta Extended Transform (HBET), a powerful network planning tool which could prove vital to network planners as the uncertainty in power systems increase. Previously, the HBET was implemented using MATLAB programming software. In this dissertation, a set of user requirements and data structure to enable efficient handling of input and output data in the HBET was developed for an open-source platform. Python programming language was chosen as the most suitable programming language to implement the program, due to its array manipulation capabilities and the plethora of information and help available online. Four scenarios were used to test the accuracy with which the tool was created. The four scenarios included a 12-bus passive feeder, a 12-bus active feeder, a 33-bus passive feeder with laterals and a 33- bus active feeder with laterals. These results were tested against the results produced by the MATLAB tool, where it was previously proven to be accurate. It was found that the percentile voltages, mean voltages and voltage standard deviations for all systems simulated in Python were identical to those simulated using the MATLAB tool, indicating that the tool had been implemented accurately, thereby validating the hypothesis.